An annotated catalogue of mites and ticks (Acari) in Fiji - Fan, Qing-Hai (Zootaxa, 2024)
Comprehending the diversity of mites and ticks is essential for gaining insight into micro-arthropod ecosystems, assisting in pest control, and maximizing utilization of beneficial mite resources. To lay a groundwork for future research endeavours, this study was prepared to provide an overview of the research chronicle and conduct an analysis of the diversity of mites and ticks recorded in Fiji. An annotated catalogue was assembled, encompassing data on the taxonomy, host/habitat, and geographical distribution of 251 species and subspecies, across 169 genera, 93 families, and four orders.